Surge and Surge Capacity in Labor and Delivery Triage Volumes - Arora, Kavita Shah; Mercer, Brian M. (American Journal of Perinatology, 2016)
Objective To understand the variation in Labor and Delivery triage and delivery volumes in an urban tertiary care center and the types of visits associated with this variability.Study Design Retrospective descriptive study from the electronic medical record of 7,678 women presenting to Labor and Delivery Triage.Results Overall, there was a sixfold variation in Labor and Delivery triage visits (mean: 21, SD: 5.7, range: 6–36), with the least and most busy days having 28.6% and 171.4% of mean volume. Volumes varied 3.8- to 17-fold on weekdays and 4- to 11-fold on weekends. Significant variation in volume and triage evaluation type also occurred through the day, with admission for delivery as the predominate reason between 2 to 10 am, and outpatient assessments predominating thereafter (p < 0.001).Conclusion There is substantial variation in daily and hourly Labor and Delivery triage activity. If not planned for, this variability could strain available resources and negatively impact care. Further study of the effect of surges in Labor and Delivery triage and delivery volumes on pregnancy outcomes and of optimal methods to improve surge capacity in the Labor and Delivery setting are needed.
Keywords: surge; surge capacity; quality; obstetrical triage; patient safety